Complex View to Racing Car Upright Design and Manufacturing - Mesicek, Jakub; Richtar, Michal; Petru, Jana; Pagac, Marek; Kutiova, Kristyna (Manufacturing Technology Journal, 2018)
This paper describes selected aspects of design, optimization and manufacturing process of racing car's upright. Uprights described in this paper are formula student car's uprights. Formula Student is an international competition between university students, which must design and build a new prototype of the car each year, according to the FSAE rules. Uprights for most racing cars, formula student cars included, must meet wide specter of different requirements, like minimal weight, minimal stiffness etc. The first part of this contribution is concerned to design requirements and boundary conditions definition problematics like different uprights types. The following parts describe the material selection and possible optimization for the design and manufacture of the new uprights for the formula car. Manufacturing and final assembly of the part will be described.
Keywords: Upright; FEM; Manufacturing Technology; Racing Car; Aluminum Alloy